Role of Transition Metal Sulphates in the Corrosion of 1100 Aluminium in Hydrochloric Acid - Yadav, P.N.S.; Singh, A.K. (Asian Journal of Chemistry, 2010)
The corrosion behaviour of 1100 aluminum in 10% hydrochloric acid has been studied in the presence of transition metal sulphates such as iron. cobalt, nickel, copper and zinc sulphate using galvanostatic and weight loss methods. The concentrations of added metal sulphates were 50, 100 and 500 ppm. It has been observed that iron and zinc sulphates retard the corrosion at all concentrations whereas nickel and copper inhibit the reaction of aluminium in hydrochloric acid up to 100 ppm concentration. Cobalt sulphate accelerates corrosion at all studied concentrations. Polarisation studies reveal the fact that iron and zinc are effective on cathodic sites.